The rentability of the second and third production cycle of the eucalyptus (corymbia angophora) in alto Tietê community - Paula, Ronaldo Damião de (2020)
Over the years, the paper and cellulose industry in Alto Tietê community kept the eucalypt production system in partners with local farmers. However, the costs of the integrated systems were very higher, and contribute to the industry adopted the new strategy like investment in production mechanization in areas plains and most far. This hit the local market with eucalyptus devaluation. Thus, this paper aims to analyze the strategy applied by local farmers to reduce eucalypt production costs. The case study was carried out in the Salesópolis community, São Paulo, as an exploratory research to comprehend the impact of paper and cellulose industry change made in the local community. The results showed that the total cost estimated to first production cycle was 1.8 most than the second cycle and the rentability in 6.5 years was de 1,92% less than other cycles. The third production cycle showed downs in land rentability, almost 18.5% less than the second cycle and 16.5% less than the first cycle. Therefore, the eucalypt production in the Alto Tietê community already was a big business and income source to local farmers and with eucalypt market devaluation and the cost increase of production and operation, the farmers had opted by the maintenance of the third cycle of production even not being the most profitable.